Differential Contribution of P5CS Isoforms to Stress Tolerance in Arabidopsis - Funck, Dietmar; Baumgarten, Lukas; Stift, Marc; von Wirén, Nicolaus; Schönemann, Luise (Frontiers in Plant Science, 2020)
Proline accumulation is a widespread response of plants to salt stress as well as drought and cold stress. In most plant species, two isoforms of pyrroline-5-carboxylate synthetase (P5CS) catalyse the first step in proline biosynthesis from glutamate. In Arabidopsis, these isoforms differ in their spatial and temporal expression patterns, suggesting sub-functionalisation. P5CS1 has been identified as the major contributor to stress-induced proline accumulation, whereas P5CS2 has been considered important for embryo development and growth. In contrast to previous results, our analysis of P5CS1- and P5CS2-GFP fusion proteins indicates that both enzymes were exclusively localised in the cytosol. The comparison of the susceptibility of p5cs1 and p5cs2 mutants to infection with Pseudomonas syringae and salt stress provided novel information on the contribution of the two P5CS isoforms to proline accumulation and stress tolerance. In agreement with previous studies, salt-stressed p5cs1 mutants accumulated very little proline, indicating that P5CS1 contributed more to stress-induced proline accumulation, whereas its impact on stress tolerance was rather weak. Germination and establishment of p5cs2 mutants were impaired under ambient conditions, further supporting that P5CS2 is most important for growth and development, whereas its contribution to stress-induced proline accumulation was smaller than that of P5CS1. In contrast to p5cs1 mutants or wildtype plants, p5cs2 mutants were only weakly affected by sudden exposure to a high NaCl concentration. These findings show that proline content, which was intermediate in leaves of p5cs2 mutants, was not directly correlated with stress tolerance in our experiments. In rosettes of NaCl-exposed p5cs2 mutants, nearly no accumulation of Na+ was observed and the plants showed neither chlorosis nor reduction of photosynthesis. Based on these data, we suggest a function of P5CS2 or P5CS2-mediated proline synthesis in regulating Na+ accumulation in leaves and thereby salt stress tolerance.